Intermediate filaments in synovial lining cells in rheumatoid arthritis and other arthritides are of vimentin type. Issue 1 (February 1982) - Osung, O A; Chandra, M; Holborow, E J
Abstract : Cryostat section of synovial tissue from patients with rheumatoid arthritis, ankylosing spondylitis, osteoarthrosis, pigmented villonodular synovitis, and from a normal knee were studied by indirect immunofluorescence with guinea-pig antibodies to the intermediate filament proteins prekeratin, vimentin, and desmin. Staining for vimentin, but absence of prekeratin and desmin, was demonstrated in synovial lining cells. Antivimentin antibody also stained synovial tissue fibroblasts and vascular endothelial lining cells. The intensity of fluorescent staining for vimentin broadly correlated with cellular proliferative activity at these 3 sites.